HIV INFECTED CHILDREN’S AND YOUNG RIGHT TO HEALTH IN ROMANIA - Daniela CALTEA (Cross-Cultural Management Journal, 2014)

(untitled)
The study was based on finding the characteristics of the process of acknowledging the right to the best health status of HIV infected children and adolescence in Romania from their perspective. The aim I was following with this study was the identification and analysis of the risks the HIV infected youth are exposed to when claiming specialised medical treatment. In this respect I focused on the degree of acknowledgement to their right of health received. I obtained my data after conducting life story interviews with youth from the counties of Iasi and Constanta and the city of Bucharest. In this article I will focus on general aspects concerning HIV infection and AIDS in Romania (statistics), the legislation concerning the right to health of Romanian children and adolescence, the identification and analysis of the barriers met in the acknowledgement to this right and measures to be taken for the eradication of these barriers.